APPLICATION VACUUM THERAPY IN COMPLEX TREATMENT OF GENERAL PERIODONTITIS AND PERIODONTITIS - Petrushanko, T.; Котелевська, Н.В.; Литовченко, І.Ю.; Ніколішин, А.К. (World of Medicine and Biology, 2014)
The article offers an analysis of the long-term results of treatment of patients with different forms of apical periodontitis and patients with generalized periodontitis using vacuum techniques in the treatment. The authors introduced in clinical trials a patented method of applying vacuum that dose over time and depression, improving device using ALU-02. In clinical conditions observed 81 patients with acute purulent exacerbations of chronic and apical periodontitis, 46 patients with generalized periodontitis I and II severity of chronicity. It is proved that the use of vacuum therapy in the treatment of oral diseases is highly effective in the later periods of observation.